Political Representation of Indigenous Papuans in the Special Autonomy Era : Case Study of Local Democracy in Southwest Papua - Purnomo, Arie; Salmawati, Salmawati; Banggu, Masni (Journal of Contemporary Local Politics, 2025)
This study examines the dynamics of political representation of Indigenous Papuans (OAP) within the framework of Special Autonomy, particularly following the revision of Law No. 2 of 2021, with a focus on local democratic practices in Southwest Papua Province. The special autonomy policy was designed as an affirmative mechanism to ensure Indigenous Papuans political participation through reserved seats in district legislatures, the empowerment of the Papuan People's Assembly, and inclusive political party recruitment. However, significant implementation challenges persist at both structural and cultural levels. This research adopts a descriptive qualitative approach, utilizing in-depth interviews with customary leaders, DPRK members, youth activists, Indigenous Papuan youth, village heads, and NGO staff, alongside policy document analysis and statistical data from the Central Statistics Agency. The findings reveal that Indigenous Papuans representation in the Regional People's Representative Council and Papuan People's Assembly remains largely symbolic. Structural barriers—such as elite domination by non- Indigenous Papuans actors, money politics, and weak local institutions—hinder substantive political inclusion. Conversely, active participation in elections and development forums reflects a strong aspiration for political justice and identity recognition. This study highlights the need to strengthen the institutional role of the MRP, reform political party recruitment processes, and enhance local governance capacity in order to promote a more inclusive democratic system for Indigenous Papuans.